All the bank's men: management of the Reserve Bank of India - Simha, S. L. N. (Madras, 1975)
The BOOK throws considerable light on the manage ment of the country's central bank and the apex financial institution of the money and capital markets, namely, the Reserve Bank of India. It is both historical and interpretative. There is careful and sympathetic diagnosis and prescription, so as to make the Reserve Bank perform its functions efficiently and imaginatively. A rather unusual sort of book on a highly topical subject, intended to stimulate all-round interest in the top management of India's premier financial institution.
Keywords: Banks and banking